2018
DOI: 10.1037/cou0000267
|View full text |Cite
|
Sign up to set email alerts
|

The working alliance, beliefs about the supervisor, and counseling self-efficacy: Applying the relational efficacy model to counselor supervision.

Abstract: There is need for closer examination of how counselors' efficacy beliefs develop and function within actual counseling or supervisory relationships. We adapted Lent and Lopez's (2002) model of relational efficacy beliefs to the context of counseling supervision, examining possible linkages of counselors' self-efficacy to beliefs about how their supervisor perceives their (counselors') efficacy (termed relation-inferred self-efficacy [RISE]), beliefs about the supervisor's efficacy (other-efficacy), and percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 35 publications
3
36
0
1
Order By: Relevance
“…In this study, a score of 60 or more on tobacco-related medical knowledge was correlated the most with high self-efficacy for smoking cessation counseling. There is controversy over the connection between CSE and training ( Mehr, Ladany & Caskie, 2015 ; Mullen et al, 2015 ; Morrison & Lent, 2018 ), but this study confirmed that the teaching method may be also one of the ways to promote self-efficacy for smoking cessation counseling. Previous studies have shown that role-playing and modeling with visual images have been particularly helpful in improving CSE ( Campbell et al, 2015 ; Botelho, Gao & Jagannathan, 2019 ).…”
Section: Discussionsupporting
confidence: 55%
“…In this study, a score of 60 or more on tobacco-related medical knowledge was correlated the most with high self-efficacy for smoking cessation counseling. There is controversy over the connection between CSE and training ( Mehr, Ladany & Caskie, 2015 ; Mullen et al, 2015 ; Morrison & Lent, 2018 ), but this study confirmed that the teaching method may be also one of the ways to promote self-efficacy for smoking cessation counseling. Previous studies have shown that role-playing and modeling with visual images have been particularly helpful in improving CSE ( Campbell et al, 2015 ; Botelho, Gao & Jagannathan, 2019 ).…”
Section: Discussionsupporting
confidence: 55%
“…In recent years, studies related to counselor education in Turkey mostly focus on supervision issues (Aladağ, 2014, Atik, Arıcı, & Ergene, 2014Çetinkaya & Karaırmak, 2012;Eryılmaz & Mutlu, 2018;Meydan, 2015;Yılmaz & Voltan-Acar, 2015), peer group supervision (Atik, Çelik, Güç, & Tutal, 2016) counseling skills (Atıcı & Ulusoy, 2010) and counselor self-efficacy (Koç, 2013). In addition topics such as counselor selfefficacy (Morrison & Lent, 2018;Gallo, 2018;Özteke, Üre, & Kesici, 2015) mindfulness (Fulton & Cashwell, 2015) and attachment (Kivlighan Jr & Marmarosh, 218;Mohr, Gelso, & Hill, 2005) were studied in the literature of counselor education both in Turkey and international areas. Another important issue in counselor education -counseling anxiety-become prominent and studies in counseling anxiety (Al-Darmaki, 2004;Barbee, Scherer, & Combs, 2003;Mohr et al, 2005) revealed that anxiety toward counseling has a prominent role in counseling performance, supervisory communication and counselor self-efficacy.…”
Section: Necmettin Erbakan Universitymentioning
confidence: 99%
“…Psikolojik danışman eğitimi ile ilgili yapılan ulusal alanyazın incelendiğinde son yıllarda ülkemizde yapılan araştırmaların çoğunlukla süpervizyon (Aladağ, 2014, Atik, Arıcı ve Ergene, 2014Çetinkaya ve Kara-ırmak, 2012;Eryılmaz ve Mutlu, 2018;Meydan, 2015;Yılmaz ve Voltan-Acar, 2015), akran grup süpervizyonu (Atik, Çelik, Güç ve Tutal, 2016), danışma becerileri (Atıcı ve Ulusoy, 2010), danışmanların çalışma yaşamı kalitesi (Bozgeyikli, 2011) ve öz-yeterlik (Koç, 2013) gibi konulara odaklandığı görülmektedir. Bunun yanı sıra, danışman öz-yeterliği (Gallo, 2018;Morrison ve Lent, 2018;Özteke, Üre ve Kesici, 2015), bilinçli farkındalık (Fulton ve Cashwell, 2015) ve bağlanma (Kivlighan Jr ve Marmarosh, 2018;Mohr, Gelso ve Hill, 2005) gibi kavramlar psikolojik danışma uygulama alanının önemli çalışma konularını oluşturmaktadır. Psikolojik danışman eğitiminin önemli çalışma alanlarından bir diğeri de danışma kaygısı olarak öne çıkmaktadır.…”
unclassified
“…Obtaining data shows signs that are not very encouraging, several things that have emerged are (1) Low motivation of supervisors; (2) Absence of professional pride; (3) Acting not in accordance with the main tasks and functions; (4) Supervisors are less independent; ( 5 The existence of supervisors in the world of education has a solid foundation and is stipulated by a number of Government Regulations and Ministerial Regulations (Marsalin, 2019). As professional school supervisors, they are assigned to carry out academic and managerial supervision activities as well as mentoring and professional training activities for teachers (Maryam, 2018;Messi et al, 2018;Morrison, & Lent, 2018;Pitkänen et al, 2018). Based on the School Supervisory Workbook, there are four main tasks of supervision that professional supervisors must have, (1) carefully observing school conditions, (2) analytical acuity and synthesis, (3) accuracy and creativity in providing the necessary treatment, (4) ability good communication with each individual in the school.…”
Section: Discussion On the Professionalism Of Vocational School Supervisorsmentioning
confidence: 99%